COVID-19 vaccines reduce the risk of SARS-CoV-2 reinfection and hospitalization: Meta-analysis - Flacco, Maria Elena; Acuti Martellucci, Cecilia; Baccolini, Valentina; De Vito, Corrado; Renzi, Erika; Villari, Paolo; Manzoli, Lamberto (Frontiers in Medicine, 2022)
The addictive protection against SARS-CoV-2 reinfection conferred by vaccination, as compared to natural immunity alone, remains to be quantified. We carried out a meta-analysis to summarize the existing evidence on the association between SARS-CoV-2 vaccination and the risk of reinfection and disease. We searched MedLine, Scopus and preprint repositories up to July 31, 2022, to retrieve cohort or case-control studies comparing the risk of SARS-CoV-2 reinfection or severe/very severe COVID-19 among vaccinated (1, 2 or 3 doses) versus unvaccinated subjects, recovered from a primary episode. Data were combined using a generic inverse-variance approach. Eighteen studies, enrolling 18,132,192 individuals, were included. As compared to the unvaccinated, vaccinated subjects showed a significantly lower likelihood of reinfection (summary Odds Ratio - OR: 0.47; 95% CI: 0.42-0.54). Notably, the results did not change in studies that adjusted for potential confounders, adopting different reinfection definitions, with different predominant strains, by number of vaccine doses and follow-up duration (up to 12 months). Once reinfected, vaccinated subjects were also significantly less likely to develop a severe disease (summary OR: 0.45; 95% CI: 0.38-0.54). Although further studies on the long-term persistence of protection, under the challenge of the new circulating variants, are inevitably needed, the present meta-analysis provides solid evidence of a stronger protection of hybrid versus natural immunity, which may persist during Omicron waves and up to 12 months.